Sentiment analysis using Natural Language Processing (NLP) & deep learning - Islam, Kazi Minhazul; Reza, Md. Safkat; Yeaser, MD. Samin (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.